2009
DOI: 10.1242/dev.027334
|View full text |Cite
|
Sign up to set email alerts
|

A role for Syndecan-4 in neural induction involving ERK- and PKC-dependent pathways

Abstract: Syndecan-4 (Syn4) is a heparan sulphate proteoglycan that is able to bind to some growth factors, including FGF, and can control cell migration. Here we describe a new role for Syn4 in neural induction in Xenopus. Syn4 is expressed in dorsal ectoderm and becomes restricted to the neural plate. Knockdown with antisense morpholino oligonucleotides reveals that Syn4 is required for the expression of neural markers in the neural plate and in neuralised animal caps. Injection of Syn4 mRNA induces the cellautonomous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 86 publications
(136 reference statements)
0
34
0
1
Order By: Relevance
“…Studies on HSPG-mediated signaling have focused on syndecan-4, a transmembrane HSPG with its cytoplasmic domain capable of activating and stabilizing PKCα, and syndecan-4-dependent PKCα activation has been indicated in fibroblast growth factor signaling. 39,40 Moreover, neuronal Thy-1-induced cell spreading requires RhoA-mediated actin cytoskeleton polymerization, a suggested downstream event after syndecan-4-dependent PKCα activation. 41 Our study also indicated that the RhoA activation induced by latent heparanase is mediated by PKCα.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on HSPG-mediated signaling have focused on syndecan-4, a transmembrane HSPG with its cytoplasmic domain capable of activating and stabilizing PKCα, and syndecan-4-dependent PKCα activation has been indicated in fibroblast growth factor signaling. 39,40 Moreover, neuronal Thy-1-induced cell spreading requires RhoA-mediated actin cytoskeleton polymerization, a suggested downstream event after syndecan-4-dependent PKCα activation. 41 Our study also indicated that the RhoA activation induced by latent heparanase is mediated by PKCα.…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus, the transmembrane proteoglycan Sdc4 is co-expressed with PN1 in the early animal hemisphere of blastula and anterior neural plate of neurula embryos (Muñoz et al, 2006;Kuriyama and Mayor, 2009). Moreover, Sdc4 is a proteolytic target of HtrA1 (Hou et al, 2007).…”
Section: Pn1 Stabilizes Sdc4 Against Degradation By Htra1mentioning
confidence: 99%
“…SDC4 is highly complex by virtue of its external side chains, and thus interacts with a variety of ligands, such as vascular endothelial growth factors (VEGFs), platelet-derived growth factors (PDGFs) and fibroblast growth factors (FGFs) (4). At the cell membrane, SDC4 stabilizes the interactions between ligands and receptors by forming a ternary complex, which has been demonstrated in several signaling pathways (5,6). Proteolytic cleavage and shedding of its extracellular domain can spread FGF signaling to adjacent cells, thus regulating the local reception of FGF signaling activity (7).…”
Section: Introductionmentioning
confidence: 99%